Is gene panel sequencing more efficient than clinical‐based gene sequencing to diagnose autoinflammatory diseases? A randomized study - Rama, M. (Clin Exp Immunol, 2020)
The aim of this study was to compare the effectiveness of the gene‐panel next‐generation sequencing (NGS) strategy versus the clinical‐based gene Sanger sequencing for the genetic diagnosis of autoinflammatory diseases (AIDs). Secondary goals were to describe the gene and mutation distribution in AID patients and to evaluate the impact of the genetic report on the patient’s medical care and treatment. Patients with AID symptoms were enrolled prospectively and randomized to two arms, NGS (n = 99) (32–55 genes) and Sanger sequencing (n = 197) (one to four genes). Genotypes were classified as ‘consistent/confirmatory’, ‘uncertain significance’ or ‘non‐contributory’. The proportion of patients with pathogenic genotypes concordant with the AID phenotype (consistent/confirmatory) was significantly higher with NGS than Sanger sequencing [10 of 99 (10·1%) versus eight of 197 (4·1%)]. MEFV, ADA2 and MVK were the most represented genes with a consistent/confirmed genotype, whereas MEFV, NLRP3, NOD2 and TNFRSF1A were found in the ‘uncertain significance’ genotypes. Six months after the genetic report was sent, 54 of 128 (42·2%) patients had received effective treatment for their symptoms; 13 of 128 (10·2%) had started treatment after the genetic study. For 59 of 128 (46%) patients, the results had an impact on their overall care, independent of sequencing group and diagnostic conclusion. Targeted NGS improved the diagnosis and global care of patients with AIDs.